2020
DOI: 10.1016/j.jot.2019.08.001
|View full text |Cite
|
Sign up to set email alerts
|

A novel calcium phosphate–based nanocomposite for the augmentation of cement-injectable cannulated pedicle screws fixation: A cadaver and biomechanical study

Abstract: Background/objectiveBoth polymethylmethacrylate (PMMA) and traditional calcium phosphate–based cements have some deficiencies as augmentation materials for pedicle screw fixation. Here, a novel calcium phosphate–based nanocomposite (CPN) for the augmentation of pedicle screw fixation was developed based on previous study, and the handling properties, biomechanical performance, and biodegradation behaviour of CPN were evaluated and compared with clinical PMMA by means of a cadaver study and animal tests.Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 28 publications
2
13
0
1
Order By: Relevance
“…The goals for such materials are to play a similar or even greater biomechanical role compared with PMMA as well as to be safe and biocompatible. A novel calcium phosphate-based nanocomposite (CPN) introduced by Sun et al 20 - 22 showed satisfying biodegradability, osteoinductivity in vivo, and exhibited equal even marginally higher maximal pullout force than PMMA. The dispersion pattern of the cement within cancellous bone is crucial to the effect of augmentation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The goals for such materials are to play a similar or even greater biomechanical role compared with PMMA as well as to be safe and biocompatible. A novel calcium phosphate-based nanocomposite (CPN) introduced by Sun et al 20 - 22 showed satisfying biodegradability, osteoinductivity in vivo, and exhibited equal even marginally higher maximal pullout force than PMMA. The dispersion pattern of the cement within cancellous bone is crucial to the effect of augmentation.…”
Section: Methodsmentioning
confidence: 99%
“…Although the mechanical strength of CPN is weaker than that of PMMA, CPN has a more regular and symmetrical dispersion, which is conducive to achieving biomechanical stability similar to that of cannulated pedicle screws augmented by PMMA. 22 In addition, silicone was found to be osteoconductive and nonhazardous to surrounding tissue and shown to exhibit nonexothermic curing, which was in contrast to PMMA. 23 Schmoelz et al 24 inserted 3 mL of self-curing elastomer (silicone) into a balloon cavity prior to cannulated pedicle screw insertion, and the elastomer group underwent significantly more mean cycles until loosening under cyclic cranio-caudal loading than the PMMA during in situ augmentation (9824 ± 1982 N vs. 7401 ± 1644 N).…”
Section: Methodsmentioning
confidence: 99%
“…% сульфату барію. Як рідку фазу використовували гідрофосфат натрію 0,25 моль [44]. Останніми роками КФЦ із додаванням магнію та стронцію показали швидке схоплювання, покращену механічну міцність і гарну швидкість резорбції.…”
Section: результати та їх обговоренняunclassified
“…[9][10][11] Calcium phosphate cement (CPC) has been suggested to be a possible alternative of PMMA due to its osteoconductivity and biodegradability. 4,[12][13][14][15][16][17][18] However, its clinical application is limited by some critical issues including short setting time, poor injectability, collapse in body fluids, low mechanical strength, and high brittleness. 12,13,[19][20][21][22][23] It has been suggested that these properties could be improved by adding cohesion promoters such as poly(l-lactide-co-glycolide) acid (PLGA), 24 poly(ε-caprolactone) (PCL), poly(l-lactic acid) (PLLA), 25 chitosan, 26 and starch.…”
Section: Introductionmentioning
confidence: 99%